How to manage vertisols - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The Sustainable Management of Vertisols Edited by J K Syers, F Penning de Vries and P Nyamudeza, CABI Publishing, 2001. 320 pp. ISBN 0851994504 GBP 55 Euro 89.25